Estimate of the Percent Reduction of the Workers Hearing Loss by Doing a Training Intervention Based on BASNEF Pattern - Rohollah FALLAH MADVARI; Fereydoon LAAL; Milad ABBASI; Mohammad Reza MONAZZAM; Alireza FALLAH MADVARI (Archives of Acoustics)
If we want to provide the efficient training intervention to increase the duration of using hearing protection devices (HPDs) by workers, we need a tool that can estimate the person’s hearing threshold taking into account noise exposure level, age, and work history, and compare them with audiometry to find out the percent reduction of workers hearing loss. First, the workers noise exposure level was determined according to ISO 9612, then 4000 Hz audiometry was done to find age and work history. On basis of ISO 1999 the hearing threshold was estimated and if the hearing protection device was not used continuously and correctly, the hearing protection device's actual performance was reduced adjusted with person’s audiometry. After training intervention, the estimate was done again and was compared with the adjusted audiometry. According to ISO1999 standard estimation results, the percent reduction of the workers hearing loss level was 6.48 dB in intervention group. This level remained unchanged in control group. The mean score of hearing threshold estimation (standard ISO 1999) was statistically more significant than mean score of hearing threshold (p-value < 0.001). The results show not significant change in control group due to lack of changing of noise exposure level. In regards to the results of hearing threshold estimation based on ISO1999 and comparing with workers audiometry, it can be seen that BASNEF training intervention increases the duration of using the HPDs and it could be effective in reducing hearing threshold related to noise.